Pengaruh Buah Kundur (Benincasa hispida) dan Buah Nanas (Ananas comosus L. Merr) Rasio Serta Konsentrasi Gula Terhadap Mutu Fruit Leather - Ruka Yulia; Noni Handayani; Juliani Juliani (Jurnal Serambi Engineering, 2020)
Fruit leather is a flesh of fruit that has been crushed and dried at 50-60oC. The study aimed to determine the effect of ratio of gourd and pineapple and the addition of sugar in the production of fruit leather. The variables were analyzed for chemistry analysis and organoleptic response. Chemical analyzes performed were water content analysis and fiber content. Organoleptic responses include color, aroma, texture, and flavor. The data was analyzed by Randomized Completely Design with two factorial. The ratio of kundur and pineapple (K) those are 80:20%, 70:30%, 60:40% while (G) those are 20%, 30% and 40%. The result of this study showed that the ratio of the concentration of kundur and pineapple 80:20% while the concentration of sugar 30% (K1G2) produced fruit leather of the highest quality with a moisture content of 8.15%, fiber content of 1.882, and organoleptic response of texture 3.80 (like) , color 3,71 (like), aroma 3,58 (like), flavor 3,91 (like).